2015
DOI: 10.1590/1982-0194201500096
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados ao uso de preservativo em pessoas vivendo com HIV/AIDS

Abstract: Objective: Identify condom use in people living with HIV/AIS attended at a Specialized Care Service in STD/ HIV/AIDS and associate it with sociodemographic and behavioral variables. Methods: Cross-sectional study, involving 300 people living with HIV/AIDS between 18 and 66 years of age. Student's t-test was used for intergroup comparison. The association between condom use and the sociodemographic and behavioral factors was verified using Pearson's correlation tests and its effect was measured through the odds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…In this study, it was found that few people (29%) reported inconsistent condom use with negative or unknown HIV status, which may be corroborated by other investigations that found rates of 28.7% respectively ( 22 ) and 20.7% ( 25 ) of inconsistent condom use among PLHIV.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, it was found that few people (29%) reported inconsistent condom use with negative or unknown HIV status, which may be corroborated by other investigations that found rates of 28.7% respectively ( 22 ) and 20.7% ( 25 ) of inconsistent condom use among PLHIV.…”
Section: Discussionsupporting
confidence: 88%
“…Men who were not in domestic partnerships were more likely to be diagnosed with HIV than women, which may be related to not using condoms, as shown by a study conducted with PLWHA, of whom singles were less likely to use condoms when compared to individuals in domestic partnerships (15) . However, among married people, the use of condoms is often dispensed, as individuals, especially women, consider domestic partnerships as a protective factor against infection due to trusting their partners (17) .…”
Section: Discussionmentioning
confidence: 98%
“…Despite the higher rates among men, the reduction in the male/female ratio observed in some states reflects power relations based on female submission concerning decision-making to adopt preventive measures (14) and difficulty in negotiating condom use with partners (15) . Besides, a 1.5-fold increase in susceptibility to HIV infection is observed in women who suffer physical or sexual violence in some regions (16) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, many women who maintain an inferior relationship with the partner usually have low power of choice in their love relationships and difficulty negotiating with the partner regarding prevention, thus increasing their risk situation. They believe that because they are in a stable, trustworthy, faithful and monogamous relationship there is no risk of contracting STI/HIV/AIDS (5)(6) . Thus, the use of condoms is considerably reduced.…”
Section: Introductionmentioning
confidence: 99%